SISTEM KEKERABATAN PATRILINEAL PADA SUKU BATAK DAN SUKU BALI: KAJIAN KOMPARATIF TERHADAP PEWARISAN DAN KEDUDUKAN ANAK LAKI-LAKI - Ni Putu Eka Sri Widiani; Komang Febrianayanti Dantes; Ni Ketut Sari Adnyani (Jurnal Ilmu Hukum Sui Generis, 2025)
The patrilineal kinship system places the paternal line as the basis of identity, inheritance, and clan continuity. Both the Batak and Balinese ethnic groups adhere to pure patrilineal systems, yet they respond differently to the absence of male offspring. This comparative normative juridical research aims to examine the philosophical construction of sons’ status, compare the norms and practices of heirloom inheritance, and analyze why the Balinese can adapt through sentana rajeg while the Batak remain orthodox-absolute. The findings reveal that the Batak regard sons as sahala hasandaran, a sacred and irreplaceable pillar of the clan based on Dalihan Na Tolu and clan exogamy. The absence of sons results in the clan being considered punu, and golat property is transferred to dongan tubu, leading to high inheritance disputes. Conversely, the Balinese construct sons functionally as bearers of ayahan duties. The philosophy of desa kala patra allows the emergence of sentana rajeg and kawin nyeburin, which transform daughters into lineage successors and full heirs of heirloom property. This difference in adaptability results in significantly lower inheritance litigation in Bali. The study concludes that patrilinealism is not monolithic. The adaptive Balinese model can serve as a reference for national customary inheritance law reform to prevent the extinction of patrilineal clans while addressing gender equality demands.